Characterisation of season-wise spatial distribution of small pelagic fishery in Kerala, south-west coast of India - Das, P. H. Dhiju; Joshy, C. G.; Edwin, Leela (Indian Journal of Fisheries, 2019)
In this study, we attempted to identify and characterise the spatial variability of small pelagic fish abundance using geostatistical methods. The small pelagic fish abundance was estimated in terms of spatial parameters using generalised additive models (GAMs). The ring seine fishing grounds in the south-eastern Arabian Sea exhibited seasonal variability in distribution. Results of the study would help in prediction of the major pelagic fishing grounds for traditional fishers which would help in reducing fuel and time spent on searching for the fishing ground leading to sustainable exploitation. The prediction model can contribute to the management of pelagic fishery along the Kerala coast.